Spatial epidemiology of intimate partner violence in Kenya: a county-level clustering analysis - Masood Ali Shaikh; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2026)
Intimate partner violence (IPV) is defined as “behaviour within an intimate relationship that causes physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse and controlling behaviours”, by the World Health Organization (WHO).1 It is a human rights and public health problem that is globally pervasive. WHO reports the global prevalence of physical and/or sexual IPV as 27% in women who have ever had an intimate relationship.2 However, this metric excludes emotional/psychological IPV and is limited to women aged 15-49 years only. But there is no empirical evidence that women aged 46 and above are immune from IPV. Hence, this figure is understandably an underestimate of the true IPV prevalence. IPV has been linked to a plethora of deleterious fatal and non-fatal outcomes in women including suicide, injuries, gynaecological complications, sexually transmitted infections, adverse pregnancy outcomes and and mental health disorders.2 Continue....